The Role of Beta HPV Types and HPV-Associated Inflammatory Processes in Cutaneous Squamous Cell Carcinoma - Mircea Tampa; Cristina Iulia Mitran; Madalina Irina Mitran; Ilinca Nicolae; Adrian Dumitru; Clara Matei; Loredana Manolescu; Gabriela Loredana Popa; Constantin Caruntu; Simona Roxana Georgescu (Journal of Immunology Research)
Cutaneous squamous cell carcinoma (cSCC) is a common form of skin cancer with a complex but not fully understood pathogenesis. Recent research suggests the role of beta human papillomavirus (HPV) types and HPV-associated inflammatory processes in cSCC development. Beta HPV types are components of the normal flora; however, under the influence of certain cofactors, the virus may trigger a malignant process. Dysregulation of the immune system (chronic inflammation and immunosuppression), environmental factors (ultraviolet radiation), and genetic factors are the most important cofactors involved in beta HPV-related carcinogenesis. In addition, the oncoproteins E6 and E7 of beta HPV types differ biochemically from their counterparts in the structure of alpha HPV types, resulting in different mechanisms of action in carcinogenesis. The aim of our manuscript is to present an updated point of view on the involvement of beta HPV types in cSCC pathogenesis.